The relation of neighbouring land use type and sedimentary characteristics of fluvial sediments in tropical rivers - Wan Hanna Melini Wan Mohtar,; Siti Aminah Bassa Nawang,; Mohd Shafique Noor Rahman,; Wan Zawiah Wan Zin,; Khairul Nizam Abdul Maulud, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the relationship between land use types and sedimentary characteristics of fluvial bed at three rivers in Selangor, Malaysia; namely Sungai Tengi, Selangor and Langat. The diversity in population density and land development at the adjacent river banks gives associated dominant land use type as forest, agriculture and urban for Tengi, Selangor and Langat, respectively. Field sampling was conducted at consistent spatial locations for Tengi and Selangor, whereas for Langat, the bed sediment was taken at non-uniform spatial points due to limited access. Statistical analysis of the sediment bed mixture shows that forest dominated land gives finer bed sediment size at < 200 μm. Agriculture-type of land use increases the mean sediment size to medium sand, whereas bed material near to urbanized areas has coarser sediment size with > 650 μm. Correlation analysis proved that there is a relationship between types of land use with the mean sediment size. No distinctive correlation can be observed for sorting, skewness and kurtosis of the sediment with the types of land use.